Needs Analysis of Group-Discovery Learning Model to Improve the 21st Century Skills of High School Students - Helda, Trisna; Atmazaki, Atmazaki; Gani, Erizal (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2024)
The is a part of research and development of a learning model that emphasizes a combination of discovery learning and group learning to develop 21st century skills in learning Indonesian for senior high school students, called the Group-Discovery Learning model. This research begins with the needs and context analysis, literature review, and conceptual theory development. This type of research is quantitative. The research data was obtained by conducting interviews with 12 teachers and distributing questionnaires to 112 students from two schools (SMAN 7 Padang and SMAN 8 Padang). Data about the problems commonly faced by students and teachers as well as their needs to improve the 21st century skills in the Indonesian language learning process in high schools were obtained. The results of the needs and context analysis show that the competence of 21st century students is still relatively low in learning Indonesian, but has great potential. The literature review revealed that the Group-Discovery Learning model can improve students' critical thinking, creative thinking, collaboration, and communication. Also, it can gain overall knowledge. These findings indicate that the development of the Group-Discovery Learning model can be a solution in accommodating high school students to develop 21st century skills in learning Indonesian.